Self-organization for community resilience in an invisible agricultural community - Erwin, Anna; Silva, Chelsea A.; Ma, Zhao (Frontiers in Sustainable Food Systems, 2023)
This study investigates how self-organizing efforts by residents of informal settlements, primarily migrant and informal farmworkers, shape community resilience in Majes, a water-scarce irrigation district in the Atacama Desert of Peru. We collected 45 semi-structured interviews with residents and authorities in Majes and analyzed findings through a framework of self-organizing. Analyses revealed that self-organizing by residents of informal settlements incorporated the three components of White’s theory of Community Agency and Community Resilience, which contends that marginalized communities increase resilience by fostering a commons praxis, practicing a prefigurative politics, and developing opportunities for economic autonomy. We also found that residents self-organized into associations to increase access to resources, resulting in increased resilience. However, certain fees, corruption, and undemocratic decision-making processes can be detrimental to self-organizing. Results expand existing theories of self-organization and community resilience by highlighting how residents of informal settlements in agricultural spaces collectively organize to increase their resilience. Findings also begin to reframe narratives that describe migrants and farmworkers as powerless in the face of water scarcity, climate change, and other social-ecological risks.